Pengaruh Pemberian Pupuk Hayati Mikoriza dan Pupuk NPK Terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max (L.) Merrill) Varietas Biosoy : Kedelai, Pupuk hayati Mikoriza, NPK, Biosoy - Satria Bagus Panuntun; Sumarmi, Sumarmi; Santosa, Sartono Joko (innofarm, 2023)
The research entitled the effect of mycoriza's biofertilizer and NPK fertilizer on the growth and produce of soybean plants (Glycine max (L.) Merrill ) Biosoy varieties took place on December 7, 2022 until March 7, 2023, In crops and horticulture Sidoharjo, Kayuloko Village, Sidoharjo Subdistrict, Wonogiri District. The study aims to learn the effects of various doses of mycoriza biofertilizer and NPK fertilizer 16:16:16 for growth and resulting from Biosoy varieties. The study used a Randomized Completely Block Design (RCBD) consisting of 2 factors namely the doses of mycoriza biofertilizer (M) and the doses of NPK fertilizer 16: 16: 16 (N), each repeated 3 times. The first is the treatment of mycoriza biofertilizer with 4 tiers (M0 ) without treatment, (M1) 2.5 g / plant, (M2) 5 g / plant, and (M3) 7.5 g / plant. The second factor is the treatment of NPK fertilizer (N0) without treatment, (N1) 1 g/plant, (N2) 2 g / plant, and (N3) 3 g/plant. The parameters observed are plant high, leaves number, wet weight, dry weight, pods number, fresh pods weight, dry seeds weight, 100 dried seeds weight, and spindle seeds weight. The result of the research showed that (1) the treatment of mycoriza biofertilizer had a real impact on 100 dried seeds weight (25.97 g) and spindle seeds weight (154.23 g). (2) NPK fertilizer treatment gives a real impact on on plant high (33.17 cm), fresh pods weight (29.11 g), 100 dried seeds weight (25.97 g) and on spindle seeds weight (154.23 g). (3) The interaction of treatment between mycoriza's bio fertilizer and NPK fertilizer has a real effect (29.11 g) on the fresh pods weight and dry seeds weight (10. 43 g). (4) The best doses of both treatment is M2N2 is giving mycoriza 5 g/ plant and NPK 2 g/ plant had a impact on plant high (33.17 cm), leaves number (83.25 strands), wet weight (25.20 g), dry weight (9.18 g), pods number (29.83 fruit), fresh pods weight (29.11 g), dry seeds weight (10.43 g), 100 dried seeds weight (25.97 g). Keywords: Soybean, Mycoriza’s bio fertilizer, NPK, Biosoy